Physical and mechanical properties assessment of glass ionomer cements modified with TiO and Mg-doped hydroxyapatite nanoparticles - Bojana Ramić; Milica Cvjetićanin; Branislav Bajkin; Milan Drobac; Marija Milanović; Dragan Rajnović; Veljko Krstonošić; Đorđe Veljović (Journal of Applied Biomaterials & Functional Materials)
High viscosity glass ionomer cements (GICs) are widely used in various clinical applications, being particularly effective in atraumatic restorative treatment (ART) due to the synergistic interaction between the material and the technique. However, the inadequate mechanical properties of GICs raise concerns regarding the predictability and longevity of these restorations in areas exposed to occlusal stress. Various modifications of the powder components have been proposed to improve the mechanical strength of GICs to withstand occlusal loading during mastication. In this in vitro study, we investigated whether the nanoparticles (NPs) added to commercially available GICs could fulfill this requirement, which would likely broaden the spectrum of their potential clinical applications. Two commercially available GIC powders (Fuji IX and Ketac Molar), modified by the addition of 5 wt.% TiO 2 , MgHAp100 or MgHAp1000 NPs, were incorporated into the corresponding liquid in an appropriate ratio, and the mixed cements were evaluated in terms of fracture toughness, flexural strength, Vickers microhardness and rheological tests and compared with the original material. Fuji IX containing 5 wt.% MgHAp100 NPs had lower flexural strength, while Ketac Molar with 5 wt.% TiO 2 NPs showed increased fracture toughness. Vickers microhardness increased in Fuji IX following the addition of 5 wt.% TiO 2 and MgHAp100 but decreased in Ketac Molar comprising 5 wt.% MgHAp100 ( p  < 0.05). Achieving a predictable bond between NPs and cement matrix, as well as ensuring a uniform distribution of the NPs within the cement, are critical prerequisites for enhancing the mechanical performance of the original cement.